1998
DOI: 10.1111/j.1365-2621.1998.tb15779.x
|View full text |Cite
|
Sign up to set email alerts
|

On‐line Measurement of Residence Time Distribution in a Food Extruder

Abstract: A technique was based on electrical conductivity of material in a die, and used a series circuit consisting of a 5 mm dia die, a 10 ohm resistor, and a 15V dc power supply. Material conductivity was altered with addition of an electrolyte tracer at the feed inlet. Change in current flow was measured as a proportional voltage response across the resistor. Using a twin-screw extruder, with L/D 32:1, the RTD of rice flour at 15% moisture was determined using sodium nitrate as tracer. Under steady state, the volta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
0
5

Year Published

2000
2000
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 13 publications
(21 reference statements)
1
12
0
5
Order By: Relevance
“…Altomare and Ghossi (1986) gave a similar result for a ZSK-57 corotating twin screw extruder using rice flour. Choudhury andGuatam (1998), De Ruyck (1997), Gasner, Bigio, and Marks (1999), Gogoi and Yam (1994), , Picot (1999), Jager, van Zuilichem, Stolp, andvanÕt Riet (1988), Lee and McCarthy (1996), , and Unlu and Faller (2002) all reported the same result of decreasing mean residence time with increasing screw speed. Even though all these studies were in agreement in the inverse relationship between the mean residence time and screw speed, some of them were in conflict in terms of degree of effect of the screw speed on the mean residence time and residence time distributions compared to that of the feed rate.…”
Section: Parameter Level Relative Effects On Mean Residence Time (%)supporting
confidence: 51%
“…Altomare and Ghossi (1986) gave a similar result for a ZSK-57 corotating twin screw extruder using rice flour. Choudhury andGuatam (1998), De Ruyck (1997), Gasner, Bigio, and Marks (1999), Gogoi and Yam (1994), , Picot (1999), Jager, van Zuilichem, Stolp, andvanÕt Riet (1988), Lee and McCarthy (1996), , and Unlu and Faller (2002) all reported the same result of decreasing mean residence time with increasing screw speed. Even though all these studies were in agreement in the inverse relationship between the mean residence time and screw speed, some of them were in conflict in terms of degree of effect of the screw speed on the mean residence time and residence time distributions compared to that of the feed rate.…”
Section: Parameter Level Relative Effects On Mean Residence Time (%)supporting
confidence: 51%
“…However, increase in throughput was accompanied by a decrease in residence time and a marked decrease in the spread of RTD. Choudhury and Gautam (1998) found that an increase in feed flow rate resulted in higher and narrower peaks for RTD compared with the low feed flow rate.The objective of this study was to determine relative residence time between varying conditions of feed rate and screw speed when the ratio of feed rate to screw speed is constant. The barrel fill under these conditions was determined to evaluate the suggestion by Meuser and Wiedmann (1989) that barrel fill is approximately constant if the ratio of screw speed to feed rate is maintained.…”
mentioning
confidence: 93%
“…The selfwiping twin screws in a twin-screw extruder permit better control of the residence time distribution (RTD) than do single screws because there is no continuous channel for uninterrupted pressure flow and no stagnant zones in the lee side of the flights. The RTD is a measure of the length of time process material spends in the extruder, and the RTD data are most useful in diagnosing axial mixing phenomena in twin-screw extruders, providing the basis for scale-up and providing leads to improvement in equipment design (Todd 1975, Choudhury andGautam 1998). The RTD also gives information on the probable residence time of the particles, the degree of uniformity of the shearing on the particles, and the temperature-time combinations, factors important for preparing a product of good quality in food extrusion (De Ruyck 1997).…”
mentioning
confidence: 99%
“…In system analyses of the extrusion process, Choudhury and Gautam (1998) and Meuser and Gimmler (1992) separated all variables into three groups, namely input parameters, system parameters and product parameters. A system parameter (e.g., specific mechanical energy, heat energy input, viscous properties of melt and residence time) is defined as a parameter that links an input parameter (e.g., type of feed material, feed rate, screw speed and barrel temperature) and a product parameter (e.g., density, porosity, moisture content and elastic properties of the product).…”
Section: Introductionmentioning
confidence: 99%
“…Several attempts had been made to measure RTD online. Choudhury and Gautam (1998) developed a measurement technique based on electrical conductivity. The electrical conductivity of the melt was measured with the help of probes inserted in the extruder die, which reflected the concentration of the salt tracer.…”
Section: Introductionmentioning
confidence: 99%